Novel Associations Between METTL3 Gene Polymorphisms and Pediatric Acute Lymphoblastic Leukemia: A Five-Center Case-Control Study - Liu, Xiaoping; Huang, Libin; Huang, Ke; Yang, Lihua; Yang, Xu; Luo, Ailing; Cai, Mansi; Wu, Xuedong; Liu, Xiaodan; Yan, Yaping; Wen, Jianyun; Cai, Yun; et al. (Frontiers in Oncology, 2021)
Objective To reveal the contributing role of METTL3 gene SNPs in pediatric ALL risk. Patients and Methods A total of 808 pediatric ALL cases and 1,340 cancer-free controls from five hospitals in South China were recruited. A case-control study by genotyping three SNPs in the METTL3 gene was conducted. Genomic DNA was abstracted from peripheral blood. Three SNPs (rs1263801 C>G, rs1139130 A>G, and rs1061027 A>C) in the METTL3 gene were chosen to be detected by taqman real-time polymerase chain reaction assay. Results That rs1263801 C>G, rs1139130 A>G, and rs1061027 A>C polymorphisms were significantly associated with increased pediatric ALL risk was identified. In stratification analyses, it was discovered that rs1263801 CC, rs1061027 AA, and rs1139130 GG carriers were more likely to develop ALL in subgroups of common B-ALL, MLL gene fusion. Rs1263801 CC and rs10610257 AA carriers were more possible to increase the risk of ALL in subgroups of low hyperdiploid, and all of these three SNPs exhibited a trend toward the risk of ALL. All of these three polymorphisms were associated with the primitive/naïve lymphocytes and MRD in marrow after chemotherapy in ALL children. Rs1263801 CC and rs1139130 AA alleles provided a protective effect on MRD ≥0.01% among CCCG-treated children. As for rs1139130, AA alleles provided a protective effect on MRD in marrow ≥0.01% on 33 days and 12 weeks among CCCG-treated children, but provided a risk effect on MRD in the marrow ≥0.01% among SCCLG-treated children. As for rs1263801 CC and rs1139130 AA, these two alleles provided a protective effect on MRD in the marrow ≥0.01% among CCCG-treated children. Conclusion In this study, we revealed that METTL3 gene polymorphisms were associated with increased pediatric ALL risk and indicated that METTL3 gene polymorphisms might be a potential biomarker for choosing ALL chemotherapeutics.